(untitled) (LACCEI, 2024)
The study conducts an analysis of the scientific literature that has focused on theoretical and practical trends on metaverses and virtual worlds in the last 5 years. For this purpose, 66 articles were collected from different databases, Ebsco (46), ProQuest (11), Scielo (3), Scopus (2) and ResearchGate (4), from 2017 to 2022. The aim of the study is to determine that the metaverse and virtual worlds are one of the most important technological changes in recent years. However, it is many years away from being fully implemented in the transfer of information and interaction of people. The argument raises a topic where the Metaverse and virtual worlds have become an alternative for the transfer of knowledge and communication for different sectors